The Saudi First Classes Teachers’ Perspectives About the Theoretical Models of Teaching Reading. - Al-Khawaldeh, Mohammad; Al-Shamari, Baeq (Jordan Journal of Educational Sciences, 2017)
This study aimed at investigating the Saudi first classes teachers’ perspectives about the theoretical models of teaching reading, if there any difference according to the variables of gender, experience, specialization, and qualification. To achieve the aims of the study (The Deford Theoretical Orientation To Reading Profile( was used, that consisted of (28) items distributed on three models (Phonics, Skills, and Whole language approach models). The sample of the study consisted of (344) first classes teachers randomly selected from the schools of Al-Qurrayat Governorate in Saudi Arabia during academic year 2015/2016. The results of the study revealed that the phonics model was the dominant belief of teaching reading theoretical models, followed by skills and whole language models respectively. The results also revealed no statistical significant difference in teachers’ beliefs due to the variables of gender, educational experience, and qualification, and statistical significant difference in their beliefs about three models due to the variable of specialization in favor of the humanities field